Treatment and Potential Co-occurrence of Hip Subluxation, Patella Alta, and Medial Patellar Luxation in a Canine: Case Report - Leonardo Martins LEAL; Carlos Henrique SILVA; Pedro APARECIDO CAMPOS JÚNIOR; Gabriel Aguiar PAVILAK; Milena Dias GONÇALVES; Isaac ROMANI; Tais Harumi de Castro SASAHARA; Paola Castro MORAES (Acta Veterinaria Eurasia)
In light of the potential correlation between hip alterations and the development of patellar luxation, as well as the challenge in selecting the ideal surgical technique for each patient, the aim is to report the treatment of a 17 kg, 1-year-old, female dog of undefined breed, presenting with grade III patellar luxation, patella alta, and hip subluxation. The patient experienced clinical improvement following the implementation of several surgical techniques. An ilio-trochanteric suture was employed to stabilize the hip joint. Due to significant contracture of the rectus femoris muscle observed during the coxal approach, which impeded proper patellar positioning, a rectus femoris tenotomy was also performed. This intervention resulted in an immediate reduction in the degree of patellar luxation from III to II. Additionally, modified trochleoplasty was performed to deepen the groove. We concluded that the ilio-trochanteric suture, in conjunction with rectus femoris tenotomy, contributed to partial alignment of the quadriceps femoris muscles, enhancing stability of the hip joint and resulting in a one-degree reduction in patellar luxation. Modified trochleoplasty stabilized the patella alta. This study reinforces the correlation between hip joint positioning and the probable etiology of patellar dislocation.